Characterization of the interaction of human DNA-dependent RNA polymerases and transcription factors with RNA from the hepatitis delta virus: Novel perspectives in HDV biology - Greco-Stewart, Valerie Suzanne (University of Ottawa (Canada), 2009)
Hepatitis delta virus (HDV) is a unique pathogen comprised solely of a single-stranded RNA molecule of ∼1,700 nucleotides. It contains only one open-reading frame and lacks the polymerase necessary for its replication. RNAP II has been implicated in HDV RNA synthesis, although the involvement of additional host polymerases has also been suggested. The present study establishes the interaction of HDV RNA with RNAP II both in cells replicating HDV and in nuclear extracts. Binding of RNAP II to HDV RNA occurs at both terminal stem-loop domains of the HDV genome and antigenome. Mutations that eliminate the secondary structure or alter the primary sequence of these domains result in abrogation of the RNA-RNAP II interaction. Sequence analyses of these regions from 81 HDV isolates show maintenance of the rod structure, conservation of a CUG triplet, and a strong purine/pyrimidine polarization, indicating that these features are necessary for RNAP II recognition. Similar experiments demonstrate that RNAP I and RNAP III binding also occurs at these terminal stem-loop domains. RNAP I, RNAP II, and RNAP III each form independent complexes on HDV RNA that contain TBP, a subunit common to all polymerases. TBP also interacts with HDV RNA in infected cells, suggesting that RNAP binding to HDV RNA occurs through this shared subunit. To complement these studies, UV-crosslinking of nuclear extract containing HDV RNA was performed and mass spectrometry of the resultant RNPs led to the identification of the multifunctional protein PSF as an HDV-interacting protein. This interaction was confirmed by EMSA and co-immunoprecipitation experiments and binding was localized to both terminal domains of both polarities of HDV RNA. RNA affinity chromatography demonstrated that PSF and RNAP II are present on HDV RNA simultaneously and that HDV-RNAP II interaction is abolished in the presence of PSF-binding competitive RNAs, suggesting that PSF acts as a transcription factor that facilitates the recruitment of RNAP II to the HDV template. These data provide insight into both HDV biology and RNA promoter recognition by RNAPs, establishing a solid foundation for future investigation into mechanisms of HDV replication and alternate template utilization by DNA-dependent RNA polymerases.
Keywords: Chemistry, Biochemistry.